(untitled) (World Bulletin of Public Health, 2024)
The article substantiates a new expanded interpretation of the concept of “population hematology”. The latter is not only a hematological section of traditional population and epidemiological medicine. Its main object is the population of patients, but its uniqueness lies in the fact that its basic object is a hierarchy of nested populations: blood cells, cell clones and groups of people. The most important property in the studied samples is their heterogeneity and, moreover, the change in heterogeneity over time.